Magnetic-core-free arched MEMS inductor and preparation method
By using glass substrates and non-photosensitive polyimide coatings in a magnetic coreless three-dimensional MEMS inductor, the structure is optimized and the process steps are simplified, and the problems of complex processes, high costs and poor stability in the prior art are solved, and the problem of "complexity of processes, high costs and poor stability" is achieved. High-quality and efficient inductor preparation.
Patent Information
- Application Number
- CN202411357329.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing coreless three-dimensional MEMS inductors have complex processing technology, high production cost and poor stability.
Using glass substrates and non-photosensitive polyimide coatings, the mechanical stability is improved by optimizing the inductor structure and simplified process steps such as magnetron sputtering, photoresist treatment and electroplating to reduce process complexity and cost .
A high-quality, high-stability, magnetic core-free arch MEMS inductor is achieved, reducing production costs and process complexity, and improving production efficiency.
Smart Images

Figure CN119446714A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coreless arched MEMS inductor and a preparation method thereof, belonging to the technical field of semiconductors. Background Art
[0002] As one of the important components of microelectronic devices, coreless three-dimensional inductors are widely used in MEMS sensors, RF MEMS, and micro energy storage devices. The inductor coils wound with enameled wire are large in size, low in production efficiency, unable to accurately control the spacing between windings, and have poor repeatability. The inherent defects of traditional technology for winding inductor coils make it unable to meet existing requirements. There is an increasing demand for miniaturized inductors with small size, high production efficiency, and excellent performance based on inductor devices. Micro-nano processing technology can achieve micron or even nanometer-level precision structure manufacturing and mass production of devices, thereby overcoming the shortcomings of traditional inductor manufacturing technology. The miniaturization and precision manufacturing of inductors can be achieved using MEMS (Micro-Electro-Mechanical Systems) technology.
[0003] At present, the manufacturing of three-dimensional MEMS inductors mostly adopts processes such as UV-LIGA, TSV (Through-Silicon Vias), and DRIE (Deep Reactive Ion Etching). These processes first prepare the bottom coil, then prepare the high aspect ratio pillars through exposure, etching, electroplating and other processes, and finally prepare the top coil. The bottom and top coils need to be connected through high aspect ratio pillars to complete the preparation of the three-dimensional inductor. The manufacturing of high aspect ratio structures is difficult and the processing cost is high. It is necessary to expose and develop a specific thick photoresist for a long time to produce a structural mask, and then the pillars of tens or even hundreds of microns need to be electroplated for a long time to be prepared. This method has a cumbersome process flow and high manufacturing cost.
[0004] The photoresist thermal reflow process is a process in which the developed photoresist undergoes structural softening and deformation when heated to a temperature higher than the glass transition temperature. After the photoresist is heated, the colloid can be transformed from a rectangle to a sphere or cylinder, thereby improving the flatness of the colloid. The three-dimensional MEMS inductor can be processed by thermal reflow of the photoresist to combine the pillars and the top lines into an arc or arched coil, thereby simplifying the preparation process. Although the three-dimensional MEMS inductor prepared by the photoresist thermal reflow process eliminates the need for the preparation of high aspect ratio pillars, the photoresist, as the supporting layer of the three-dimensional inductor, is easily affected in subsequent processes, and the stress generated by the photoresist as a sacrificial layer during the removal process using degumming solutions such as acetone and NMP will reduce the mechanical stability of the inductor and even cause the inductor to rupture.
[0005] In addition, the prior art uses silicon wafers as the substrate of coreless three-dimensional inductors, but the silicon wafer substrate will increase the loss of the inductor and reduce the quality factor of the inductor. Therefore, how to use a simple, easy and low-cost process to prepare high-quality and high-stability coreless three-dimensional inductors has become a technical problem that needs to be solved. Summary of the invention
[0006] In order to solve the problems of complex processing technology, high preparation cost and poor stability of existing coreless three-dimensional MEMS inductors, the present invention provides a coreless arched MEMS inductor and a preparation method. By optimizing the structure of the coreless three-dimensional inductor, the mechanical stability of the inductor is improved, and the mass production of miniature inductors is completed.
[0007] The present invention provides a coreless arched MEMS inductor, comprising: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0008] The inductor coil comprises an inductor bottom coil and an inductor top arch coil, the fuze pad comprises a first fuze pad and a first connecting line thereof, a second fuze pad and a second connecting line thereof, the inductor bottom coil and the first fuze pad and the first fuze pad are electroplated on a glass substrate, the two ends of the inductor coil are respectively connected to the first fuze pad and the second fuze pad through a first connecting line and a second connecting line, the non-photosensitive polyimide coating is attached to the surface of the glass substrate as a supporting layer of the inductor top arch coil, the inductor top arch coil and the non-photosensitive polyimide coating are conformed, and the top surface of the fuze pad and the top surface of the inductor top arch coil are not covered by the non-photosensitive polyimide coating.
[0009] Preferably, two ends of the bottom coil of the inductor are connected to the first fuse pad and the second fuse pad respectively through a first connecting wire and a second connecting wire.
[0010] The present invention also provides a method for preparing a coreless arched MEMS inductor, the method comprising the following steps:
[0011] Step S1, cleaning the glass substrate with acetone, isopropanol, and deionized water in sequence, and drying it;
[0012] Step S2, magnetron sputtering a Ti or Ti+Cu metal seed layer on the surface of the glass substrate;
[0013] Step S3, coating a first positive photoresist on the surface of the Ti or Ti+Cu metal seed layer, drying, exposing, and developing, to obtain a coil groove at the bottom of the inductor and a first fuse pad groove, a first connecting wire groove, a second fuse pad groove, and a second connecting wire groove;
[0014] Step S4, electroplating the groove of the coil at the bottom of the inductor and the groove of the first fuse pad and the groove of the second fuse pad to obtain the coil at the bottom of the inductor and the first fuse pad, the first connecting wire, the second fuse pad, and the second connecting wire, and the two ends of the coil at the bottom of the inductor are connected to the first fuse pad and the second fuse pad respectively through the first connecting wire, the second connecting wire;
[0015] Step S5, using acetone to remove the first positive photoresist to expose the Ti or Ti+Cu seed layer, and then using an etching solution to remove the Ti or Ti+Cu seed layer;
[0016] Step S6, spin coating a layer of non-photosensitive polyimide coating, and drying; coating a layer of second positive photoresist on the surface of the non-photosensitive polyimide coating, and drying;
[0017] Step S7, through exposure and development, the support layer of the arched coil at the top of the inductor is formed, and the fuse pad is wrapped in a non-photosensitive polyimide coating, and the top of the fuse pad is exposed;
[0018] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist remaining on the surface of the non-photosensitive polyimide coating, and baking the non-photosensitive polyimide coating at high temperature in an oxygen-free environment to complete imidization;
[0019] Step S9, magnetron sputtering a Cu metal seed layer on the surface of the non-photosensitive polyimide coating;
[0020] Step S10, coating a layer of third positive photoresist on the surface of the Cu metal seed layer and drying;
[0021] Step S11, forming an arched coil groove at the top of the inductor by exposure and development;
[0022] Step S12, electroplating the groove of the arched coil at the top of the inductor to obtain the arched coil at the top of the inductor, so that the arched coil at the top of the inductor and the coil at the bottom of the inductor are closed to form a complete inductor coil 7, and achieve electrical connection;
[0023] Step S13, using acetone to remove the third positive photoresist, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer, and then using a corrosive solution to remove the Cu metal seed layer, slice and bond, to obtain a coreless arch MEMS inductor.
[0024] Preferably, in step S2, the magnetron sputtering process parameters are: Ti sputtering power is 400W~600W, Ti sputtering rate is 2.04Å / s~3.14Å / s, and thickness is 500Å~1000Å; Cu sputtering power is 300W~600W, Cu sputtering rate is 3.68Å / s~6.59Å / s, and thickness is 1000Å~2000Å.
[0025] Preferably, in step S3, AZ series positive photoresist is spin-coated or spray-coated as the first positive photoresist, and the thickness of the first positive photoresist is 5 μm~15 μm; the baking temperature is 90°C~110°C, and the baking time is 200s~350s; the exposure method is hard contact exposure, the exposure distance is 50μm~200μm, and the exposure dose is 230mj~600mj; the developing solution is an alkaline solution of tetramethylammonium hydroxide, or an organic solvent developer, and the developing time is 2min40s~4min;
[0026] In step S4, the electroplating solution is an electroplating solution containing Cu ions, the electroplating current is 0.182A~0.251A, and the electroplating time is 200s~800s;
[0027] In step S5, the immersion time of the acetone solution is 5 min to 10 min, the corrosive liquid is a Ti metal corrosive liquid, or a Ti metal corrosive liquid and a Cu metal corrosive liquid, wherein the Cu metal corrosive liquid is a mixture of nitric acid, phosphoric acid and acetic acid, and the Ti metal corrosive liquid is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 2% to 8%.
[0028] Preferably, in step S6, the thickness of the non-photosensitive polyimide coating is 45 μm~65 μm, the baking temperature is 110°C~140°C, and the baking time is 200s~300s; AZ series positive photoresist is spin-coated or spray-coated as the second positive photoresist, the thickness of the second positive photoresist is 5 μm~15 μm, the baking temperature is 90°C~110°C, and the baking time is 200s~350s.
[0029] Preferably, in step S7, the exposure method is hard contact exposure, the exposure distance is 50 μm~200 μm, the exposure dose is 230 mj~600 mj; the developing solution is an alkaline solution of tetramethylammonium hydroxide or an organic solvent developer solution, and the developing time is 3 min 20 s~4 min 40 s.
[0030] Preferably, in step S8, the concentration of propylene glycol monomethyl ether acetate solution is 99.1% to 99.9%, the soaking time is 2 min 40 s to 5 min 30 s; the baking temperature is 140° C. to 300° C., and the baking time is 6 h to 9 h.
[0031] Preferably, in step S9, the magnetron sputtering process parameters are: Cu sputtering power is 300W~600W, Cu sputtering rate is 3.68Å / s~6.59Å / s, and thickness is 500Å~1000Å;
[0032] In step S10, AZ series positive photoresist is spin-coated or spray-coated as the third positive photoresist, the thickness of the third positive photoresist is 5 μm-15 μm, the baking temperature is 90° C.-110° C., and the baking time is 200 s-350 s;
[0033] In step S11, the exposure mode is hard contact exposure, the exposure distance is 50 μm~200 μm, the exposure dose is 230 mj~600 mj, the developing solution is an alkaline solution of tetramethyl ammonium hydroxide or an organic solvent developer solution, and the developing time is 2 min 40 s~4 min.
[0034] Preferably, in step S12, the electroplating solution is an electroplating solution containing Cu ions, the electroplating current is 0.147A~0.212A, and the electroplating time is 240s~600s;
[0035] In step S13, the acetone soaking time is 5 min to 10 min, and the etching liquid is a Cu metal etching liquid, which is a mixture of nitric acid, phosphoric acid and acetic acid.
[0036] Compared with the prior art, the advantages of the present invention are:
[0037] 1. The present invention uses a glass wafer as a substrate. The low substrate loss of the glass wafer will not interfere with the operation of the electronic components. Its excellent physical properties and chemical stability are conducive to the long-term use of the electronic components.
[0038] 2. The present invention uses non-photosensitive polyimide as the arched coil support layer at the top of the inductor. The imidized non-photosensitive polyimide has excellent physical properties. As the support layer of the coil, it can significantly improve the mechanical stability of the three-dimensional inductor. In addition, the non-photosensitive polyimide is used as the inductor support layer rather than the sacrificial layer, which eliminates the risk of the inductor breaking due to deformation stress during the removal of the colloid.
[0039] 3. The present invention selects wet development for non-photosensitive polyimide coatings. Compared with dry etching, wet etching has stronger drilling ability, and the side walls of the processed graphics often have a certain slope rather than a nearly vertical cross-section. This feature can improve the uniformity of subsequent thin film deposition and the step coverage of the pattern. Compared with traditional photoresists, non-photosensitive polyimides have higher viscosity. During the development process, thicker or too viscous adhesive layers will slow down the diffusion rate of the developer, making it easier for the side walls to form a slope during the development process. By controlling the development time of non-photosensitive polyimide to form a slope on its side walls, in the subsequent step of applying positive photoresist, the positive photoresist will be evenly distributed on the slope, and the preparation of the three-dimensional coil can be completed by one-time electroplating, thereby eliminating the dependence of the three-dimensional inductor on the high aspect ratio structure.
[0040] 4. Compared with MEMS inductors prepared based on UV-LIGA, TSV and DRIE processes, the arched coil prepared by the present invention does not require long-term electroplating to form a column structure with a high aspect ratio, thereby reducing process cost and complexity while improving the production efficiency of the device. Compared with the existing preparation process under the same conditions, the preparation time of this preparation method is shortened by 15% to 20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0042] Figure 1 It is an axonometric schematic diagram of a coreless arched MEMS inductor of the present invention;
[0043] Figure 2 Schematic diagram of the three views of the coreless arched MEMS inductor of the present invention;
[0044] Figure 3 This is a schematic diagram of the effect of step S1 of preparing a coreless arched MEMS inductor according to the present invention;
[0045] Figure 4 This is a schematic diagram of the effect of step S2 of preparing a coreless arched MEMS inductor according to the present invention;
[0046] Figure 5 This is a schematic diagram of the effect of step S3 of preparing a coreless arched MEMS inductor according to the present invention;
[0047] Figure 6 This is a schematic diagram of the effect of step S4 of preparing a coreless arched MEMS inductor according to the present invention;
[0048] Figure 7 This is a schematic diagram of the effect of step S5 of preparing a coreless arched MEMS inductor according to the present invention;
[0049] Figure 8 This is a schematic diagram of the effect of step S6 of preparing a coreless arched MEMS inductor according to the present invention;
[0050] Fig. 9 This is a schematic diagram of the effect of step S7 of preparing a coreless arched MEMS inductor according to the present invention;
[0051] Fig.10 This is a schematic diagram of the effect of step S8 of preparing a coreless arched MEMS inductor according to the present invention;
[0052] Fig.11This is a schematic diagram of the effect of step S9 of preparing a coreless arched MEMS inductor according to the present invention;
[0053] Fig.12 This is a schematic diagram of the effect of step S10 of preparing a coreless arched MEMS inductor according to the present invention;
[0054] Fig.13 This is a schematic diagram of the effect of step S11 of preparing a coreless arched MEMS inductor according to the present invention;
[0055] Fig.14 This is a schematic diagram of the effect of step S12 of preparing a coreless arched MEMS inductor according to the present invention;
[0056] Fig.15 This is a schematic diagram of the effect of step S13 of preparing a coreless arched MEMS inductor according to the present invention;
[0057] Fig.16 This is a test result diagram of the coreless arched MEMS inductor prepared in Example 1 of the present invention;
[0058] In the figure, a-top view; b-main view; c-left view; 1-glass substrate; 2-Ti / Cu metal seed layer; 3-first positive photoresist; 4-inductor bottom coil groove; 5-first fuse pad groove; 50-first connecting line groove; 6-second fuse pad groove; 60-second connecting line groove; 7-inductor coil; 70-inductor bottom coil; 71-inductor top arched coil; 8-first fuse pad; 80-first connecting line; 9-second fuse pad; 90-second connecting line; 10-non-photosensitive polyimide coating; 11-second positive photoresist; 12-Cu metal seed layer; 13-third positive photoresist; 14-inductor top arched coil groove. DETAILED DESCRIPTION
[0059] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is described in detail below in conjunction with specific embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.
[0060] The present invention provides a coreless arched MEMS inductor, comprising: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0061] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arch coil 71, the fuse pad includes a first fuse pad 8 and a first connecting line 80 thereof, a second fuse pad 9 and a second connecting line 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor coil 7 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting line 80 and a second connecting line 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arch coil 71, the inductor top arch coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arch coil 71 are not covered by the non-photosensitive polyimide coating 10. Figure 1 This is an axonometric diagram of the coreless arched MEMS inductor of the present invention. Figure 2 Schematic diagram of three views of the coreless arched MEMS inductor of the present invention.
[0062] Specifically, two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting wire 80 and a second connecting wire 90 respectively.
[0063] It should be noted that when using silicon wafer as the substrate of the coreless three-dimensional inductor, the silicon wafer substrate will increase the loss of the inductor and reduce the quality factor of the inductor, while the lower substrate loss of the glass wafer will not interfere with the operation of the electronic components. Its excellent physical properties and chemical stability are conducive to the long-term use of electronic components. Therefore, the present invention uses a glass wafer as the substrate.
[0064] The present invention also provides a method for preparing a coreless arched MEMS inductor, comprising the following steps:
[0065] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0066] Step S2, magnetron sputtering a Ti or Ti+Cu metal seed layer 2 on the surface of the glass substrate 1;
[0067] Step S3, coating a first positive photoresist 3 on the surface of the Ti or Ti+Cu metal seed layer 2, drying, exposing, and developing, to obtain the coil groove 4 and the first fuse pad groove 5, the first connecting wire groove 50, the second fuse pad groove 6, and the second connecting wire groove 60 at the bottom of the inductor;
[0068] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0069] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti or Ti+Cu seed layer 2, and then using an etching solution to remove the Ti or Ti+Cu seed layer 2;
[0070] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0071] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0072] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0073] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0074] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0075] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0076] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0077] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0078] It should be noted that, in step S1, Figure 3 Schematic diagram of the effect of step S1 of preparing a coreless arched MEMS inductor according to the present invention.
[0079] In step S2, the magnetron sputtering process parameters are: Ti sputtering power is 400W~600W, Ti sputtering rate is 2.04Å / s~3.14Å / s, and thickness is 500Å~1000Å; Cu sputtering power is 300W~600W, Cu sputtering rate is 3.68Å / s~6.59Å / s, and thickness is 1000Å~2000Å.
[0080] It should be noted that the bonding effect between the glass wafer and the metal layer is an important factor in selecting the type of metal for the seed layer. Cu, as one of the most commonly used metals, has poor bonding with the glass wafer. If Cu is selected as the seed layer of the substrate, it will easily fall off due to poor bonding, increasing the risk of process failure. To solve this problem, it is more feasible to use Ti, which has better bonding with the glass wafer, as the seed layer of the substrate. Therefore, first, a layer of Ti is magnetron sputtered as the base layer. Since the bottom coil and fuse pad of the inductor are prepared by electroplating Cu, the growth rate of the same metal will be faster, so a layer of Cu can be selectively magnetron sputtered on the surface of the Ti layer.
[0081] Figure 4 Schematic diagram of the effect of step S2 of preparing a coreless arched MEMS inductor according to the present invention.
[0082] In step S3, AZ series positive photoresist is spin-coated or spray-coated as the first positive photoresist, and the thickness of the first positive photoresist 3 is 5μm~15μm; the baking temperature is 90℃~110℃, the baking time is 200s~350s, the exposure method is hard contact exposure, the exposure distance is 50μm~200μm, the exposure dose is 230mj~600mj, and the developing solution is an alkaline solution containing TMAH group, i.e., tetramethylammonium hydroxide, or an organic solvent developer, and the developing time is 2min40s~4min. Figure 5 Schematic diagram of the effect of step S3 of preparing a coreless arched MEMS inductor according to the present invention.
[0083] In step S4, the electroplating solution is an electroplating solution containing Cu ions, the electroplating current is 0.182A~0.251A, and the electroplating time is 200s~800s. Figure 6 Schematic diagram of the effect of step S4 of preparing a coreless arched MEMS inductor according to the present invention.
[0084] In step S5, the immersion time of the acetone solution is 5 min to 10 min, the corrosive liquid is a Ti metal corrosive liquid, or a Ti metal corrosive liquid and a Cu metal corrosive liquid, wherein the Cu metal corrosive liquid is a mixture of nitric acid, phosphoric acid and acetic acid, and the Ti metal corrosive liquid is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 2% to 8%. Figure 7 Schematic diagram of the effect of step S5 of preparing a coreless arched MEMS inductor according to the present invention.
[0085] In step S6, non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 45μm~65μm, the baking temperature is 110℃~140℃, and the baking time is 200s~300s; AZ series positive photoresist is spin-coated or sprayed as the second positive photoresist, the thickness of the second positive photoresist 11 is 5μm~15μm, the baking temperature is 90℃~110℃, and the baking time is 200s~350s. Figure 8 Schematic diagram of the effect of step S6 of preparing a coreless arched MEMS inductor according to the present invention.
[0086] In step S7, the exposure method is hard contact exposure, the exposure distance is 50μm~200μm, the exposure dose is 230mj~600mj, the developing solution is an alkaline solution or an organic solvent developer solution containing TMAH group, i.e., tetramethylammonium hydroxide, and the developing time is determined according to the surface shape of the non-photosensitive polyimide coating 10 to be formed, such as 3min20s~4min40s. Fig. 9 Schematic diagram of the effect of step S7 of preparing a coreless arched MEMS inductor according to the present invention.
[0087] It should be noted that in steps S6 and S7, non-photosensitive polyimide is used as the arched coil support layer at the top of the inductor, and wet development is selected. Compared with dry etching, wet etching has stronger drilling ability, and the side wall of the pattern processed by it often has a certain slope rather than a nearly vertical cross section. This feature can improve the uniformity of subsequent thin film deposition and the step coverage of the pattern. Compared with traditional photoresists, non-photosensitive polyimide has a higher viscosity. During the development process, a thicker or too viscous glue layer will slow down the diffusion speed of the developer, making it easier for the side wall to form an inclined surface during the development process. By controlling the development time of non-photosensitive polyimide to form an inclined surface on its side wall, in the subsequent step S10 of spin-coating positive photoresist, the positive photoresist will be evenly distributed on the inclined surface, and the preparation of the three-dimensional coil can be completed by one-time electroplating, thereby eliminating the dependence of the three-dimensional inductor on the high aspect ratio structure. In addition, the imidized non-photosensitive polyimide has excellent physical properties. As the support layer of the coil, it can significantly improve the mechanical stability of the three-dimensional inductor. Moreover, the non-photosensitive polyimide serves as the inductor support layer rather than the sacrificial layer, eliminating the risk of inductor rupture due to deformation stress during the removal process of the colloid.
[0088] In step S8, the concentration of propylene glycol monomethyl ether acetate solution is 99.1%~99.9%, and the immersion time is 2min40s~5min30s; the baking temperature is 140℃~300℃, and the baking time is 6h~9h. It should be noted that the baking temperature is a gradually increasing baking process starting from 140℃ and ending at 300℃, and is not fixed at a certain temperature between 140℃~300℃. Fig.10Schematic diagram of the effect of step S8 of preparing a coreless arched MEMS inductor according to the present invention.
[0089] In step S9 , the sputtering process parameters are: Cu sputtering power is 300 W to 600 W, Cu sputtering rate is 3.68 Å / s to 6.59 Å / s, and thickness is 500 Å to 1000 Å. Fig.11 Schematic diagram of the effect of step S9 of preparing a coreless arched MEMS inductor according to the present invention.
[0090] In step S10, AZ series positive photoresist is spin-coated or spray-coated as the third positive photoresist. The thickness of the third positive photoresist 13 is 5 μm-15 μm, the baking temperature is 90° C.-110° C., and the baking time is 200 s-350 s. Fig.12 Schematic diagram of the effect of step S10 of preparing a coreless arched MEMS inductor according to the present invention.
[0091] In step S11, the exposure method is hard contact exposure, the exposure distance is 50μm~200μm, the exposure dose is 230mj~600mj, the developing solution is an alkaline solution or an organic solvent developer solution containing TMAH group, i.e. tetramethylammonium hydroxide, and the developing time is 2min40s~4min. Fig.13 Schematic diagram of the effect of step S11 of preparing a coreless arched MEMS inductor according to the present invention.
[0092] In step S12, the electroplating solution is an electroplating solution containing Cu ions, the electroplating current is 0.147A~0.212A, and the electroplating time is 240s~600s. Fig.14 Schematic diagram of the effect of step S12 of preparing a coreless arched MEMS inductor according to the present invention.
[0093] In step S13, the acetone soaking time is 5 minutes to 10 minutes, and the etching liquid is a Cu metal etching liquid, which is a mixture of nitric acid, phosphoric acid and acetic acid. Fig.15 Schematic diagram of the effect of step S13 of preparing a coreless arched MEMS inductor according to the present invention.
[0094] The prepared coreless arch MEMS inductor was tested for performance using an E4990A vector network analyzer. The performance test included inductance value and quality factor. The test frequency was 1KHz ~ 100MHz, and the measurement interval was 0.2 MHz. Fig.16 : is a test result diagram of the coreless arched MEMS inductor of Example 1 of the present invention, Fig.16 The inductance value and quality factor curve in FIG. 1 are within the normal range and belong to a normal inductance curve, indicating that the performance of the coreless arched MEMS inductor prepared by the present invention can meet the use requirements.
[0095] Compared with MEMS inductors prepared based on UV-LIGA, TSV and DRIE processes, the arched coil prepared by the present invention does not require long-term electroplating to form a column structure with a high aspect ratio, thereby reducing process cost and complexity while improving the production efficiency of the device. Compared with existing preparation processes under the same conditions, the preparation time of this preparation method is shortened by 15% to 20%.
[0096] Example 1
[0097] A coreless arched MEMS inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0098] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arch coil 71, the fuse pad includes a first fuse pad 8 and a first connecting line 80 thereof, a second fuse pad 9 and a second connecting line 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor coil 7 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting line 80 and a second connecting line 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arch coil 71, the inductor top arch coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arch coil 71 are not covered by the non-photosensitive polyimide coating 10.
[0099] A method for preparing a coreless arched MEMS inductor comprises the following steps:
[0100] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0101] Step S2, magnetron sputtering a Ti metal seed layer 2 on the surface of the glass substrate 1;
[0102] The sputtering process parameters are: Ti sputtering power is 400 W, Ti sputtering rate is 2.04 Å / s, and thickness is 500 Å.
[0103] Step S3, coating a first positive photoresist 3 on the surface of the Ti metal seed layer 2, drying, exposing, and developing, to obtain the coil groove 4 at the bottom of the inductor and the first fuse pad groove 5, the first connecting wire groove 50, the second fuse pad groove 6, and the second connecting wire groove 60;
[0104] Spin-coat AZ series positive photoresist as the first positive photoresist, the thickness of the first positive photoresist 3 is 5μm; the baking temperature is 90°C, the baking time is 200s, the exposure method is hard contact exposure, the exposure distance is 50μm, the exposure dose is 230mj, the developing solution is an alkaline solution containing TMAH group, i.e., tetramethylammonium hydroxide, and the developing time is 2min40s.
[0105] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0106] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.182 A, and the electroplating time is 200 s.
[0107] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti seed layer 2, and then using an etching solution to remove the Ti seed layer 2;
[0108] The immersion time of the acetone solution is 5 minutes. The etching liquid is a Ti metal etching liquid. The Ti metal etching liquid is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 2%.
[0109] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0110] Non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 45 μm, the baking temperature is 110° C., and the baking time is 200 s; AZ series positive photoresist is spin-coated as the second positive photoresist, the thickness of the second positive photoresist 11 is 5 μm, the baking temperature is 90° C., and the baking time is 200 s.
[0111] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0112] The exposure method is hard contact exposure, the exposure distance is 50 μm, the exposure dose is 230 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 3 min 20 s.
[0113] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0114] The concentration of propylene glycol monomethyl ether acetate solution is 99.1%, the immersion time is 2min40s; the baking temperature is 140℃~300℃, and the baking time is 6h.
[0115] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0116] The sputtering process parameters are: Cu sputtering power is 300W, Cu sputtering rate is 3.68Å / s, and thickness is 500Å.
[0117] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0118] AZ series positive photoresist is spin-coated as the third positive photoresist. The thickness of the third positive photoresist 13 is 5 μm, the baking temperature is 90° C., and the baking time is 200 s.
[0119] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0120] The exposure method is hard contact exposure, the exposure distance is 50 μm, the exposure dose is 230 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 2 min 40 s.
[0121] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0122] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.147 A, and the electroplating time is 240 s.
[0123] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0124] The acetone immersion time is 5 minutes, and the etching liquid is a Cu metal etching liquid, which is made by mixing nitric acid, phosphoric acid, and acetic acid.
[0125] Example 2
[0126] A coreless arched MEMS inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0127] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arched coil 71, the fuse pad includes a first fuse pad 8 and a first connecting wire 80 thereof, a second fuse pad 9 and a second connecting wire 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor bottom coil 70 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting wire 80 and a second connecting wire 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arched coil 71, the inductor top arched coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arched coil 71 are not covered by the non-photosensitive polyimide coating 10.
[0128] A method for preparing a coreless arched MEMS inductor comprises the following steps:
[0129] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0130] Step S2, magnetron sputtering a Ti metal seed layer 2 on the surface of the glass substrate 1;
[0131] The sputtering process parameters are: Ti sputtering power is 600 W, Ti sputtering rate is 3.14 Å / s, and thickness is 1000 Å.
[0132] Step S3, coating a first positive photoresist 3 on the surface of the Ti metal seed layer 2, drying, exposing, and developing, to obtain the coil groove 4 at the bottom of the inductor and the first fuse pad groove 5, the first connecting wire groove 50, the second fuse pad groove 6, and the second connecting wire groove 60;
[0133] AZ series positive photoresist is sprayed as the first positive photoresist, and the thickness of the first positive photoresist 3 is 15μm; the baking temperature is 110℃, the baking time is 350s, the exposure method is hard contact exposure, the exposure distance is 200μm, the exposure dose is 600mj, the developing solution is an organic solvent developer, and the developing time is 4min.
[0134] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0135] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.251 A, and the electroplating time is 800 s.
[0136] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti seed layer 2, and then using an etching solution to remove the Ti seed layer 2;
[0137] The immersion time of the acetone solution is 10 minutes. The etching liquid is a Ti metal etching liquid. The Ti metal etching liquid is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 8%.
[0138] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0139] Non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 65 μm, the baking temperature is 140° C., and the baking time is 300 s; AZ series positive photoresist is sprayed as the second positive photoresist, the thickness of the second positive photoresist 11 is 15 μm, the baking temperature is 110° C., and the baking time is 350 s.
[0140] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0141] The exposure method is hard contact exposure, the exposure distance is 200 μm, the exposure dose is 600 mj, the developing solution is an organic solvent developer solution, and the developing time is 4 min 40 s.
[0142] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0143] The concentration of propylene glycol monomethyl ether acetate solution is 99.9%, the immersion time is 5min30s; the baking temperature is 140℃~300℃, and the baking time is 9h.
[0144] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0145] The sputtering process parameters are: Cu sputtering power is 600W, Cu sputtering rate is 6.59Å / s, and thickness is 1000Å.
[0146] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0147] AZ series positive photoresist is sprayed as the third positive photoresist. The thickness of the third positive photoresist 13 is 15 μm, the baking temperature is 110° C., and the baking time is 350 s.
[0148] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0149] The exposure method is hard contact exposure, the exposure distance is 200 μm, the exposure dose is 600 mj, the developing solution is an organic solvent developer solution, and the developing time is 4 minutes.
[0150] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0151] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.212 A, and the electroplating time is 600 s.
[0152] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0153] The acetone immersion time is 10 minutes, and the etching liquid is a Cu metal etching liquid, which is made by mixing nitric acid, phosphoric acid, and acetic acid.
[0154] Example 3
[0155] A coreless arched MEMS inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0156] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arch coil 71, the fuse pad includes a first fuse pad 8 and a first connecting line 80 thereof, a second fuse pad 9 and a second connecting line 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor coil 7 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting line 80 and a second connecting line 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arch coil 71, the inductor top arch coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arch coil 71 are not covered by the non-photosensitive polyimide coating 10.
[0157] A method for preparing a coreless arched MEMS inductor comprises the following steps:
[0158] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0159] Step S2, magnetron sputtering a Ti metal seed layer 2 on the surface of the glass substrate 1;
[0160] The sputtering process parameters are: Ti sputtering power is 500 W, Ti sputtering rate is 2.59 Å / s, and thickness is 750 Å.
[0161] Step S3, coating a first positive photoresist 3 on the surface of the Ti metal seed layer 2, drying, exposing, and developing, to obtain the coil groove 4 at the bottom of the inductor and the first fuse pad groove 5, the first connecting wire groove 50, the second fuse pad groove 6, and the second connecting wire groove 60;
[0162] Spin-coat AZ series positive photoresist as the first positive photoresist, the thickness of the first positive photoresist 3 is 10μm; the baking temperature is 100℃, the baking time is 275s, the exposure method is hard contact exposure, the exposure distance is 125μm, the exposure dose is 415mj, the developing solution is an alkaline solution containing TMAH group, i.e. tetramethylammonium hydroxide, and the developing time is 3min20s.
[0163] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0164] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.217 A, and the electroplating time is 500 s.
[0165] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti seed layer 2, and then using an etching solution to remove the Ti seed layer 2;
[0166] The immersion time of the acetone solution is 7.5 minutes. The etching solution is a Ti metal etching solution. The Ti metal etching solution is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 5%.
[0167] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0168] Non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 55 μm, the baking temperature is 125° C., and the baking time is 250 s; AZ series positive photoresist is spin-coated as the second positive photoresist, the thickness of the second positive photoresist 11 is 10 μm, the baking temperature is 100° C., and the baking time is 275 s.
[0169] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0170] The exposure method is hard contact exposure, the exposure distance is 125 μm, the exposure dose is 415 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 4 minutes.
[0171] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0172] The concentration of propylene glycol monomethyl ether acetate solution is 99.5%, and the immersion time is 4min5s; the baking temperature is 140℃~300℃, and the baking time is 7.5h.
[0173] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0174] The sputtering process parameters are: Cu sputtering power is 450W, Cu sputtering rate is 5.14Å / s, and thickness is 750Å.
[0175] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0176] AZ series positive photoresist is spin-coated as the third positive photoresist. The thickness of the third positive photoresist 13 is 10 μm, the baking temperature is 100° C., and the baking time is 275 s.
[0177] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0178] The exposure method is hard contact exposure, the exposure distance is 125 μm, the exposure dose is 415 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 3 min 20 s.
[0179] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0180] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.180 A, and the electroplating time is 420 s.
[0181] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0182] The acetone immersion time is 7.5 minutes, and the etching liquid is a Cu metal etching liquid, which is made by mixing nitric acid, phosphoric acid, and acetic acid.
[0183] Example 4
[0184] A coreless arched MEMS inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0185] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arch coil 71, the fuse pad includes a first fuse pad 8 and a first connecting line 80 thereof, a second fuse pad 9 and a second connecting line 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor coil 7 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting line 80 and a second connecting line 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arch coil 71, the inductor top arch coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arch coil 71 are not covered by the non-photosensitive polyimide coating 10.
[0186] A method for preparing a coreless arched MEMS inductor comprises the following steps:
[0187] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0188] Step S2, magnetron sputtering a Ti+Cu metal seed layer 2 on the surface of the glass substrate 1;
[0189] The sputtering process parameters are: Ti sputtering power is 400W, Ti sputtering rate is 2.04Å / s, and thickness is 500Å; Cu sputtering power is 300W, Cu sputtering rate is 3.68Å / s, and thickness is 1000Å.
[0190] Step S3, coating a first positive photoresist 3 on the surface of the Ti+Cu metal seed layer 2, drying, exposing, and developing, to obtain a coil groove 4 at the bottom of the inductor and a first fuse pad groove 5, a first connecting wire groove 50, a second fuse pad groove 6, and a second connecting wire groove 60;
[0191] Spin-coat AZ series positive photoresist as the first positive photoresist, the thickness of the first positive photoresist 3 is 5μm; the baking temperature is 90°C, the baking time is 200s, the exposure method is hard contact exposure, the exposure distance is 50μm, the exposure dose is 230mj, the developing solution is an alkaline solution containing TMAH group, i.e., tetramethylammonium hydroxide, and the developing time is 2min40s.
[0192] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0193] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.182 A, and the electroplating time is 200 s.
[0194] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti+Cu seed layer 2, and then using an etching solution to remove the Ti+Cu seed layer 2;
[0195] The immersion time of the acetone solution is 5 minutes. The etching solutions are Ti metal etching solution and Cu metal etching solution. The Ti metal etching solution is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 2%. The Cu metal etching solution is a mixture of nitric acid, phosphoric acid and acetic acid.
[0196] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0197] Non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 45 μm, the baking temperature is 110° C., and the baking time is 200 s; AZ series positive photoresist is spin-coated as the second positive photoresist, the thickness of the second positive photoresist 11 is 5 μm, the baking temperature is 90° C., and the baking time is 200 s.
[0198] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0199] The exposure method is hard contact exposure, the exposure distance is 50 μm, the exposure dose is 230 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 3 min 20 s.
[0200] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0201] The concentration of propylene glycol monomethyl ether acetate solution is 99.1%, the immersion time is 2min40s; the baking temperature is 140℃~300℃, and the baking time is 6h.
[0202] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0203] The sputtering process parameters are: Cu sputtering power is 300W, Cu sputtering rate is 3.68Å / s, and thickness is 500Å.
[0204] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0205] AZ series positive photoresist is spin-coated as the third positive photoresist. The thickness of the third positive photoresist 13 is 5 μm, the baking temperature is 90° C., and the baking time is 200 s.
[0206] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0207] The exposure method is hard contact exposure, the exposure distance is 50 μm, the exposure dose is 230 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 2 min 40 s.
[0208] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0209] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.147 A, and the electroplating time is 240 s.
[0210] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0211] The acetone immersion time is 5 minutes, and the etching liquid is a Cu metal etching liquid, which is made by mixing nitric acid, phosphoric acid, and acetic acid.
[0212] Example 5
[0213] A coreless arched MEMS inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0214] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arched coil 71, the fuse pad includes a first fuse pad 8 and a first connecting wire 80 thereof, a second fuse pad 9 and a second connecting wire 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor bottom coil 70 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting wire 80 and a second connecting wire 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arched coil 71, the inductor top arched coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arched coil 71 are not covered by the non-photosensitive polyimide coating 10.
[0215] A method for preparing a coreless arched MEMS inductor comprises the following steps:
[0216] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0217] Step S2, magnetron sputtering a Ti+Cu metal seed layer 2 on the surface of the glass substrate 1;
[0218] The sputtering process parameters are: Ti sputtering power is 600W, Ti sputtering rate is 3.14Å / s, and thickness is 1000Å; Cu sputtering power is 600W, Cu sputtering rate is 6.59Å / s, and thickness is 2000Å.
[0219] Step S3, coating a first positive photoresist 3 on the surface of the Ti+Cu metal seed layer 2, drying, exposing, and developing, to obtain a coil groove 4 at the bottom of the inductor and a first fuse pad groove 5, a first connecting wire groove 50, a second fuse pad groove 6, and a second connecting wire groove 60;
[0220] AZ series positive photoresist is sprayed as the first positive photoresist, and the thickness of the first positive photoresist 3 is 15μm; the baking temperature is 110℃, the baking time is 350s, the exposure method is hard contact exposure, the exposure distance is 200μm, the exposure dose is 600mj, the developing solution is an organic solvent developer, and the developing time is 4min.
[0221] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0222] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.251 A, and the electroplating time is 800 s.
[0223] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti+Cu seed layer 2, and then using an etching solution to remove the Ti+Cu seed layer 2;
[0224] The immersion time of the acetone solution is 10 minutes. The etching solutions are Ti metal etching solution and Cu metal etching solution. The Ti metal etching solution is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 8%. The Cu metal etching solution is a mixture of nitric acid, phosphoric acid and acetic acid.
[0225] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0226] Non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 65 μm, the baking temperature is 140° C., and the baking time is 300 s; AZ series positive photoresist is sprayed as the second positive photoresist, the thickness of the second positive photoresist 11 is 15 μm, the baking temperature is 110° C., and the baking time is 350 s.
[0227] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0228] The exposure method is hard contact exposure, the exposure distance is 200 μm, the exposure dose is 600 mj, the developing solution is an organic solvent developer solution, and the developing time is 4 min 40 s.
[0229] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0230] The concentration of propylene glycol monomethyl ether acetate solution is 99.9%, the immersion time is 5min30s; the baking temperature is 140℃~300℃, and the baking time is 9h.
[0231] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0232] The sputtering process parameters are: Cu sputtering power is 600W, Cu sputtering rate is 6.59Å / s, and thickness is 1000Å.
[0233] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0234] AZ series positive photoresist is sprayed as the third positive photoresist. The thickness of the third positive photoresist 13 is 15 μm, the baking temperature is 110° C., and the baking time is 350 s.
[0235] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0236] The exposure method is hard contact exposure, the exposure distance is 200 μm, the exposure dose is 600 mj, the developing solution is an organic solvent developer solution, and the developing time is 4 minutes.
[0237] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0238] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.212 A, and the electroplating time is 600 s.
[0239] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0240] The acetone immersion time is 10 minutes, and the etching liquid is a Cu metal etching liquid, which is made by mixing nitric acid, phosphoric acid, and acetic acid.
[0241] Example 6
[0242] A coreless arched MEMS inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating;
[0243] Specifically, the inductor coil 7 includes an inductor bottom coil 70 and an inductor top arch coil 71, the fuse pad includes a first fuse pad 8 and a first connecting line 80 thereof, a second fuse pad 9 and a second connecting line 90 thereof, the inductor bottom coil 70 and the first fuse pad 8 and the first fuse pad 9 are electroplated on a glass substrate 1, and two ends of the inductor coil 7 are respectively connected to the first fuse pad 8 and the second fuse pad 9 through a first connecting line 80 and a second connecting line 90, and a non-photosensitive polyimide coating 10 is attached to the surface of the glass substrate 1 as a supporting layer of the inductor top arch coil 71, the inductor top arch coil 71 and the non-photosensitive polyimide coating 10 follow the shape, and the top surface of the fuse pad and the top surface of the inductor top arch coil 71 are not covered by the non-photosensitive polyimide coating 10.
[0244] A method for preparing a coreless arched MEMS inductor comprises the following steps:
[0245] Step S1, cleaning the glass substrate 1 with acetone, isopropanol and deionized water in sequence, and drying it;
[0246] Step S2, magnetron sputtering a Ti+Cu metal seed layer 2 on the surface of the glass substrate 1;
[0247] The sputtering process parameters are: Ti sputtering power is 500W, Ti sputtering rate is 2.59Å / s, and thickness is 750Å; Cu sputtering power is 450W, Cu sputtering rate is 5.14Å / s, and thickness is 1500Å.
[0248] Step S3, coating a first positive photoresist 3 on the surface of the Ti+Cu metal seed layer 2, drying, exposing, and developing, to obtain a coil groove 4 at the bottom of the inductor and a first fuse pad groove 5, a first connecting wire groove 50, a second fuse pad groove 6, and a second connecting wire groove 60;
[0249] Spin-coat AZ series positive photoresist as the first positive photoresist, the thickness of the first positive photoresist 3 is 10μm; the baking temperature is 100℃, the baking time is 275s, the exposure method is hard contact exposure, the exposure distance is 125μm, the exposure dose is 415mj, the developing solution is an alkaline solution containing TMAH group, i.e. tetramethylammonium hydroxide, and the developing time is 3min20s.
[0250] Step S4, electroplating the inductor bottom coil groove 4 and the first fuse pad groove 5 and the second fuse pad groove 6 to obtain the inductor bottom coil 70 and the first fuse pad 8, the first connecting wire 80, the second fuse pad 9 and the second connecting wire 90, and the two ends of the inductor bottom coil 70 are connected to the first fuse pad 8 and the second fuse pad 9 through the first connecting wire 80 and the second connecting wire 90 respectively;
[0251] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.217 A, and the electroplating time is 500 s.
[0252] Step S5, using acetone to remove the first positive photoresist 3 to expose the Ti+Cu seed layer 2, and then using an etching solution to remove the Ti+Cu seed layer 2;
[0253] The immersion time of the acetone solution is 7.5 minutes. The etching solutions are Ti metal etching solution and Cu metal etching solution. The Ti metal etching solution is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 5%. The Cu metal etching solution is a mixture of nitric acid, phosphoric acid and acetic acid.
[0254] Step S6, spin coating a layer of non-photosensitive polyimide coating 10, and drying; coating a layer of second positive photoresist 11 on the surface of the non-photosensitive polyimide coating 10, and drying;
[0255] Non-photosensitive polyimide is spin-coated, the thickness of the non-photosensitive polyimide coating 10 is 55 μm, the baking temperature is 125° C., and the baking time is 250 s; AZ series positive photoresist is spin-coated as the second positive photoresist, the thickness of the second positive photoresist 11 is 10 μm, the baking temperature is 100° C., and the baking time is 275 s.
[0256] Step S7, through exposure and development, the support layer of the arched coil 71 at the top of the inductor is formed, and the fuse pad is wrapped in the non-photosensitive polyimide coating 10, and the top of the fuse pad is exposed;
[0257] The exposure method is hard contact exposure, the exposure distance is 125 μm, the exposure dose is 415 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 4 minutes.
[0258] Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist 11 remaining on the surface of the non-photosensitive polyimide coating 10, and baking the non-photosensitive polyimide coating 10 at high temperature in an oxygen-free environment to complete imidization;
[0259] The concentration of propylene glycol monomethyl ether acetate solution is 99.5%, and the immersion time is 4min5s; the baking temperature is 140℃~300℃, and the baking time is 7.5h.
[0260] Step S9, magnetron sputtering a Cu metal seed layer 12 on the surface of the non-photosensitive polyimide coating 10;
[0261] The sputtering process parameters are: Cu sputtering power is 450W, Cu sputtering rate is 5.14Å / s, and thickness is 750Å.
[0262] Step S10, coating a layer of third positive photoresist 13 on the surface of the Cu metal seed layer 12, and drying;
[0263] AZ series positive photoresist is spin-coated as the third positive photoresist. The thickness of the third positive photoresist 13 is 10 μm, the baking temperature is 100° C., and the baking time is 275 s.
[0264] Step S11, forming an arched coil groove 14 at the top of the inductor by exposure and development;
[0265] The exposure method is hard contact exposure, the exposure distance is 125 μm, the exposure dose is 415 mj, the developing solution is an alkaline solution containing TMAH group, namely tetramethylammonium hydroxide, and the developing time is 3 min 20 s.
[0266] Step S12, electroplating the inductor top arched coil groove 14 to obtain the inductor top arched coil 71, so that the inductor top arched coil 71 and the inductor bottom coil 70 are closed to form a complete inductor coil 7, and achieve electrical connection;
[0267] The electroplating solution is a Cu ion-containing electroplating solution, the electroplating current is 0.180 A, and the electroplating time is 420 s.
[0268] Step S13, using acetone to remove the third positive photoresist 13, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer 12, and then using a corrosive solution to remove the Cu metal seed layer 12, slice and bond, to obtain a coreless arch MEMS inductor.
[0269] The acetone immersion time is 7.5 minutes, and the etching liquid is a Cu metal etching liquid, which is made by mixing nitric acid, phosphoric acid, and acetic acid.
[0270] The coreless arched MEMS inductors prepared in Examples 1 to 6 were subjected to performance tests using an E4990A vector network analyzer. The performance tests included inductance and quality factor. The test frequency was 1 KHz to 100 MHz, and the measurement interval was 0.2 MHz. The coreless arched MEMS inductor prepared in Example 1 was as follows: Fig.16 The inductance and quality factor curves shown are within the normal range.
[0271] Compared with MEMS inductors prepared based on UV-LIGA, TSV and DRIE processes, the arched coils prepared in Examples 1 to 6 do not require long-term electroplating to form a column structure with a high aspect ratio, thereby reducing process cost and complexity while improving the production efficiency of the device. Compared with existing preparation processes under the same conditions, the preparation time of Examples 1 to 6 is shortened by 15% to 20%.
[0272] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope determined by the claims.
Claims
1. A coreless arched MEMS inductor, characterized in that: The inductor comprises: a glass substrate, an inductor coil, a fuse pad, and a non-photosensitive polyimide coating; The inductor coil comprises an inductor bottom coil and an inductor top arched coil, the fuze pad comprises a first fuze pad and a first connecting wire thereof, a second fuze pad and a second connecting wire thereof, the inductor bottom coil and the first fuze pad and the first fuze pad are electroplated on the glass substrate, the two ends of the inductor coil are respectively connected to the first fuze pad and the second fuze pad through the first connecting wire and the second connecting wire, the non-photosensitive polyimide coating is attached to the surface of the glass substrate as a supporting layer of the inductor top arched coil, the inductor top arched coil and the non-photosensitive polyimide coating are conformed, and the top surface of the fuze pad and the top surface of the inductor top arched coil are not covered by the non-photosensitive polyimide coating.
2. The method according to claim 1, characterized in that: Two ends of the bottom coil of the inductor are connected to the first fuse pad and the second fuse pad through the first connecting wire and the second connecting wire, respectively.
3. A method for preparing a coreless arched MEMS inductor, characterized in that: The method is used to prepare the coreless arched MEMS inductor as claimed in claim 1, and the method comprises the following steps: Step S1, cleaning the glass substrate with acetone, isopropanol, and deionized water in sequence, and drying it; Step S2, magnetron sputtering a Ti or Ti+Cu metal seed layer on the surface of the glass substrate; Step S3, coating a first positive photoresist on the surface of the Ti or Ti+Cu metal seed layer, drying, exposing, and developing, to obtain a coil groove at the bottom of the inductor and a first fuse pad groove, a first connecting wire groove, a second fuse pad groove, and a second connecting wire groove; Step S4, electroplating the groove of the coil at the bottom of the inductor and the groove of the first fuse pad and the groove of the second fuse pad to obtain the coil at the bottom of the inductor and the first fuse pad, the first connecting wire, the second fuse pad, and the second connecting wire, and the two ends of the coil at the bottom of the inductor are connected to the first fuse pad and the second fuse pad respectively through the first connecting wire, the second connecting wire; Step S5, using acetone to remove the first positive photoresist to expose the Ti or Ti+Cu seed layer, and then using an etching solution to remove the Ti or Ti+Cu seed layer; Step S6, spin coating a layer of non-photosensitive polyimide coating, and drying; coating a layer of second positive photoresist on the surface of the non-photosensitive polyimide coating, and drying; Step S7, through exposure and development, the support layer of the arched coil at the top of the inductor is formed, and the fuse pad is wrapped in a non-photosensitive polyimide coating, and the top of the fuse pad is exposed; Step S8, using propylene glycol monomethyl ether acetate solution to remove the second positive photoresist remaining on the surface of the non-photosensitive polyimide coating, and baking the non-photosensitive polyimide coating at high temperature in an oxygen-free environment to complete imidization; Step S9, magnetron sputtering a Cu metal seed layer on the surface of the non-photosensitive polyimide coating; Step S10, coating a layer of third positive photoresist on the surface of the Cu metal seed layer and drying; Step S11, forming an arched coil groove at the top of the inductor by exposure and development; Step S12, electroplating the groove of the arched coil at the top of the inductor to obtain the arched coil at the top of the inductor, so that the arched coil at the top of the inductor and the coil at the bottom of the inductor are closed to form a complete inductor coil 7, and achieve electrical connection; Step S13, using acetone to remove the third positive photoresist, and sequentially using isopropyl alcohol and deionized water to clean the surface to expose the Cu metal seed layer, and then using a corrosive solution to remove the Cu metal seed layer, slice and bond, to obtain a coreless arch MEMS inductor.
4. The method according to claim 3, characterized in that In step S2, the magnetron sputtering process parameters are: Ti sputtering power is 400W~600W, Ti sputtering rate is 2.04Å / s~3.14Å / s, and thickness is 500Å~1000Å; Cu sputtering power is 300W~600W, Cu sputtering rate is 3.68Å / s~6.59Å / s, and thickness is 1000Å~2000Å.
5. The method according to claim 3, characterized in that: In the step S3, AZ series positive photoresist is spin-coated or spray-coated as the first positive photoresist, and the thickness of the first positive photoresist is 5 μm~15 μm; the baking temperature is 90°C~110°C, and the baking time is 200s~350s; the exposure method is hard contact exposure, the exposure distance is 50μm~200μm, and the exposure dose is 230mj~600mj; the developing solution is an alkaline solution of tetramethylammonium hydroxide, or an organic solvent developer, and the developing time is 2min40s~4min; In step S4, the electroplating solution is an electroplating solution containing Cu ions, the electroplating current is 0.182A~0.251A, and the electroplating time is 200s~800s; In step S5, the immersion time of the acetone solution is 5 min to 10 min, the corrosive liquid is a Ti metal corrosive liquid, or a Ti metal corrosive liquid and a Cu metal corrosive liquid, wherein the Cu metal corrosive liquid is a mixture of nitric acid, phosphoric acid and acetic acid, and the Ti metal corrosive liquid is an HF aqueous solution, wherein the mass percentage of HF in the aqueous solution is 2% to 8%.
6. The method according to claim 3, characterized in that: In the step S6, the thickness of the non-photosensitive polyimide coating is 45 μm to 65 μm, the baking temperature is 110° C. to 140° C., and the baking time is 200 s to 300 s; AZ series positive photoresist is spin-coated or spray-coated as the second positive photoresist, the thickness of the second positive photoresist is 5 μm to 15 μm, the baking temperature is 90° C. to 110° C., and the baking time is 200 s to 350 s.
7. The method according to claim 3, characterized in that In the step S7, the exposure method is hard contact exposure, the exposure distance is 50 μm-200 μm, the exposure dose is 230 mj-600 mj; the developing solution is an alkaline solution of tetramethyl ammonium hydroxide or an organic solvent developer solution, and the developing time is 3 min 20 s-4 min 40 s.
8. The method according to claim 3, characterized in that In the step S8, the concentration of the propylene glycol monomethyl ether acetate solution is 99.1% to 99.9%, the soaking time is 2 min 40 s to 5 min 30 s; the baking temperature is 140° C. to 300° C., and the baking time is 6 h to 9 h.
9. The method according to claim 3, characterized in that: In the step S9, the magnetron sputtering process parameters are: Cu sputtering power is 300W~600W, Cu sputtering rate is 3.68Å / s~6.59Å / s, thickness is 500Å~1000Å; In the step S10, AZ series positive photoresist is spin-coated or spray-coated as the third positive photoresist, the thickness of the third positive photoresist is 5 μm-15 μm, the baking temperature is 90° C.-110° C., and the baking time is 200 s-350 s; In the step S11, the exposure method is hard contact exposure, the exposure distance is 50 μm~200 μm, the exposure dose is 230 mj~600 mj, the developing solution is an alkaline solution of tetramethyl ammonium hydroxide or an organic solvent developer solution, and the developing time is 2 min 40 s~4 min.
10. The method according to claim 3, characterized in that: In the step S12, the electroplating solution is an electroplating solution containing Cu ions, the electroplating current is 0.147A~0.212A, and the electroplating time is 240s~600s; In the step S13, the acetone soaking time is 5 min to 10 min, and the etching solution is a Cu metal etching solution, which is a mixture of nitric acid, phosphoric acid and acetic acid.
Citation Information
Patent Citations
Minitype orthogonal exciting fluxgate sensor
CN103439674A
Micro-array type fluxgate sensor
CN104614690A
Thin-film micro-inductor with graphical planar magnetic core and double-layer planar spiral structure and preparation method of thin-film micro-inductor
CN106298180A
Micro-magnetic fluxgate sensor based on sewing type core structure
CN109358301A
Integrated inductor and preparation method thereof
CN115424811A